An Atypical Case of Taravana Syndrome in a Breath-Hold Underwater Fishing Champion: A Case Report - Andrea Cortegiani; Grazia Foresta; Giustino Strano; Maria Teresa Strano; Francesca Montalto; Domenico Garbo; Santi Maurizio Raineri (Case Reports in Medicine)
Dysbaric accidents are usually referred to compressed air-supplied diving. Nonetheless, some cases of decompression illness are known to have occurred among breath-hold (BH) divers also, and they are reported in the medical literature. A male BH diver (57 years old), underwater fishing champion, presented neurological disorders as dizziness, sensory numbness, blurred vision, and left frontoparietal pain after many dives to a 30–35 meters sea water depth with short surface intervals. Symptoms spontaneously regressed and the patient came back home. The following morning, pain and neurological impairment occurred again and the diver went by himself to the hospital where he had a generalized tonic-clonic seizure and lost consciousness. A magnetic resonance imaging of the brain disclofsed a cortical T1-weighted hypointense area in the temporal region corresponding to infarction with partial hemorrhage. An early hyperbaric oxygen therapy led to prompt resolution of neurological findings. All clinical and imaging characteristics were referable to the Taravana diving syndrome, induced by repetitive prolonged deep BH dives. The reappearance of neurological signs after an uncommon 21-hour symptom-free interval may suggest an atypical case of Taravana syndrome.